Evaluation of Pea (Pisum sativum L.) Varieties for Growth, Yield and Quality of Seed Under Malwa Region of Madhya Pradesh - SHYAM KUMAR PATIDAR; SS KUSHWAH; OP SINGH; IS NARUKA (Seed Research, 2026)
Twelve pea varieties V1 - Arka Kartik, V2-Azad Pea-3, V3 - Pusa Pragati, V4 - Kashi Shakti, V5 - Kashi Samarth, V6- Arkel, V7- Kashi Mukti, V8- Kashi Uday, V9- Kashi Nandini, V10-Matar Ageta-6, V11-Arka Ajit and V12-Bonneville were evaluated for growth, yield and seed quality in randomized block design with four replications. Findings revealed that maximum plant height, number of leaves per plant, number of branches per plant, fresh weight of plant and dry weight of plant were recorded in Kashi Shakti. Highest number of root nodules was observed with Kashi Shakti under the study. Matar Ageta-6 recorded minimum days taken to 50% flowering. Maximum number of pod per plant was found with variety Kashi Shakti. Maximum number of seeds per pod and length of pod were recorded in variety Pusa Pragati. Highest shelling percentage was observed in case of variety Matar Ageta-6 which was followed by Kashi Shakti, Kashi Samarth and Arka Kartik with non significant difference.Maximum seed yield per hectare was found in variety Kashi Shakti which was followed by Kashi Samarth, Pusa Pragati and Kashi Uday with non significant differences. Rest of the varieties differed significantly from Kashi Shakti. Maximum germination percentage was recorded in Kashi Mukti which was at par to Arkel, Kashi Shakti, Kashi Uday, Azad Pea-3, Arka Ajit. Kashi Nandini, Kashi Samarth, Pusa Pragati, Matar Ageta-6 and Bonneville. Maximum 100 seed weight (20.88g) was observed in Matar Ageta-6, followed by Kashi Samarth, Pusa Pragati, Bonneville, Arka Kartik and Arka Ajit with non significant differences. Seed vigour index was highest with Arkel (3662.25) which was at par with Matar Ageta-6, Kashi Shakti, Kashi Mukti, Azad Pea-3, Arka Ajit. Kashi Uday and Arka Kartik.